The evolution of global farming land: facts and interpretations - Headey, Derek D. (Wiley, 2017)
Although land plays a crucially important role in economic development and structural transformation, the causes and consequences of the evolution of farming land have received scant attention in recent decades. In this article, I document global and regional changes in aggregate agricultural land use, per capita land use, and average farm sizes. The spatial distribution of global farming land has changed dramatically, with developed countries substantially reducing their share of global agricultural land, and land‐abundant developing countries substantially increasing their share. In per capita terms, we see a rather different pattern, with average farm sizes increasing in rich and more commercialized agricultural systems, and generally declining or staying constant in poorer and less commercialized systems. These outcomes are the result of complex processes that are not always well understood. I conclude the article by suggesting new, or neglected, areas of research that would facilitate a better understanding of these critically important developments.